2018
DOI: 10.1007/s10886-018-0935-3
|View full text |Cite
|
Sign up to set email alerts
|

Feminization of Male Brown Treesnake Methyl Ketone Expression via Steroid Hormone Manipulation

Abstract: Pheromones are useful tools for the management of invasive invertebrates, but have proven less successful in field applications for invasive vertebrates. The brown treesnake, Boiga irregularis, is an invasive predator that has fundamentally altered the ecology of Guam. The development of control tools to manage Boiga remains ongoing. Skin-based, lipophilic pheromone components facilitate mating in brown treesnakes, with females producing the same long-chain, saturated and monounsaturated (ketomonoene) methyl k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…This enzyme regulates the production of ketone bodies in the mitochondria [19]. Ketone bodies can be used by cells as compensatory energy sources during fast tumor growth [36] and converted to acetyl CoA and transduced to Krebs cycle (reviewed by [37]) or further used for cholesterol synthesis [38,39]. Saraon and colleagues showed that HMGCS2 was about 9-fold higher in LNCaPabl compared to parental LNCaP cells, suggesting a link between elevated expression of HMGCS2 and CRPC [40].…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme regulates the production of ketone bodies in the mitochondria [19]. Ketone bodies can be used by cells as compensatory energy sources during fast tumor growth [36] and converted to acetyl CoA and transduced to Krebs cycle (reviewed by [37]) or further used for cholesterol synthesis [38,39]. Saraon and colleagues showed that HMGCS2 was about 9-fold higher in LNCaPabl compared to parental LNCaP cells, suggesting a link between elevated expression of HMGCS2 and CRPC [40].…”
Section: Discussionmentioning
confidence: 99%
“…Trappability is also related to the ability of an individual to detect chemical stimuli from baited traps. BTS use olfactory cues to find prey in baited traps (Shivik, 1998), and male BTS also use olfactory cues (i.e., female pheromones) to find mates (Greene et al, 2001;Parker, Patel, Zachry, & Kimball, 2018) and elicit courtship (Greene & Mason, 1998). Therefore, it is likely that males with better chemosensory abilities will not only find baited traps more frequently but also have greater success in finding and acquiring mates.…”
Section: Predictors Of Ams and Arsmentioning
confidence: 99%
“…The isolation of these skin lipids has utility in research focused on evolutionary patterns and mechanisms of chemical communication, in addition to understanding the waterproofing role of lipids in the evolution of terrestrial life 2,3,4 . Further, many reptiles, especially squamates (lizards, snakes), are invasive species of concern in sensitive ecosystems, and the development of pheromone-based lures to improve trapping and removal is ongoing 5,6 . The impermeability of reptile skin facilitates the extraction of the lipids present to obtain relatively pure extractions of a potentially robust source of chemical signals.…”
Section: Introductionmentioning
confidence: 99%
“…The impermeability of reptile skin facilitates the extraction of the lipids present to obtain relatively pure extractions of a potentially robust source of chemical signals. The principle steps for quantifying reptile skin lipids in the described protocol include extraction, total lipid determination, and fractionation via column chromatography 1,6,7 . The methods have been used routinely as they yield bioactive isolates that explain much about mate choice and selection, especially in snakes 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation